2019
DOI: 10.3390/su11236803
|View full text |Cite
|
Sign up to set email alerts
|

A Machine Learning Portfolio Allocation System for IPOs in Korean Markets Using GA-Rough Set Theory

Abstract: An initial public offering (IPO) is a type of public offering in which a company’s shares are sold to institutional and individual investors. While the majority of studies on IPOs have focused on the efficiency of raising capital and price adequacy in IPOs, studies on portfolio allocation strategies for IPO stocks are relatively scarce. This paper develops a machine learning investment strategy for IPO stocks based on rough set theory and a genetic algorithm (GA-rough set theory). To reduce issues of informati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…More precisely, the authors conduct a classification task by developing models which try to identify IPOs with first-day returns of 50% or higher. In a similar fashion, several other studies use financial variables as inputs in machine learning algorithms to classify whether the IPOs will realize positive or negative first-day returns (Cheng et al, 2007;Chen et al, 2010;Kim et al, 2019).…”
Section: Machine Learning Approach Of Ipo Underpricingmentioning
confidence: 99%
See 2 more Smart Citations
“…More precisely, the authors conduct a classification task by developing models which try to identify IPOs with first-day returns of 50% or higher. In a similar fashion, several other studies use financial variables as inputs in machine learning algorithms to classify whether the IPOs will realize positive or negative first-day returns (Cheng et al, 2007;Chen et al, 2010;Kim et al, 2019).…”
Section: Machine Learning Approach Of Ipo Underpricingmentioning
confidence: 99%
“…As a second robustness test, we adopt two alternative sample splits for our training and testing datasets. First, we select 70% of our data as the training set, and the remaining 30% as the testing set (Veganzones and Severin, 2018;Kim et al, 2019). Second, we select 75% of our data as the training set, and the remaining 25% as the testing set (Gogas et al, 2018).…”
Section: Prediction With a Combination Of Lexicon Features And Financial Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies proposed a pattern matching trading system using DTW to predict exchange rates and stock prices [20][21][22][23]. Additionally, GA has been used for predicting stock indices, real estate auction prices and appraisals, and was also used to optimize IPO investment strategies or trading strategies that hedge options [24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, few efforts to increase IC have been made by practitioners and academics. Researchers have recently reported that scientific methodology can be used to improve the accuracy of transition pattern recognition [11,12]. The hidden Markov model (HMM) shows good predictive power for transition pattern recognition [13].…”
Section: Introductionmentioning
confidence: 99%